2019
DOI: 10.1136/bmj.l5456
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation for heart failure can improve quality of life and fitness

Abstract: The studyTaylor RS, Walker S, Ciani O, et al. Exercise-based cardiac rehabilitation for chronic heart failure: the EXTRAMATCH II individual participant data meta-analysis. Health Technol Assess 2019;23:1-98.This project was funded by the NIHR Health Technology Assessment Programme (project number 15/80/30).To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000803/cardiac-rehabilitation-for-heart-failure-can-improve-quality-of-life-and-fitness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…1). In addition to secondary prevention and improvement in cardiovascular prognosis, a focus of modern cardiac rehabilitation has been the drive to improve patient wellbeing and health-related quality of life [2][3][4] .Introduced in the late 1960s, the recommendation for the provision of cardiac rehabilitation was, at that time, confined to low-risk patients who had survived an acute myocardial infarction (MI). With the development of an evidence base over the past two decades supporting the benefits of cardiac rehabilitation, contemporary clinical guidelines now routinely recommend the referral to comprehensive cardiac rehabilitation across a wider range of cardiac diagnoses, including acute coronary syndrome, heart failure with reduced ejection fraction (HFrEF) and coronary revascularization (percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) surgery).An important emphasis of contemporary guidelines, including the 2020 position statement from the European Association of Preventive Cardiology (EAPC) 5 , the 2017 guidance from the British Association for Cardiovascular Prevention and Rehabilitation 6 and the 2020 position statement from the Secondary Prevention and Rehabilitation Section of EAPC, is the importance of quality assurance in cardiac rehabilitation delivery 7 (Box 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). In addition to secondary prevention and improvement in cardiovascular prognosis, a focus of modern cardiac rehabilitation has been the drive to improve patient wellbeing and health-related quality of life [2][3][4] .Introduced in the late 1960s, the recommendation for the provision of cardiac rehabilitation was, at that time, confined to low-risk patients who had survived an acute myocardial infarction (MI). With the development of an evidence base over the past two decades supporting the benefits of cardiac rehabilitation, contemporary clinical guidelines now routinely recommend the referral to comprehensive cardiac rehabilitation across a wider range of cardiac diagnoses, including acute coronary syndrome, heart failure with reduced ejection fraction (HFrEF) and coronary revascularization (percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) surgery).An important emphasis of contemporary guidelines, including the 2020 position statement from the European Association of Preventive Cardiology (EAPC) 5 , the 2017 guidance from the British Association for Cardiovascular Prevention and Rehabilitation 6 and the 2020 position statement from the Secondary Prevention and Rehabilitation Section of EAPC, is the importance of quality assurance in cardiac rehabilitation delivery 7 (Box 1).…”
mentioning
confidence: 99%
“…1). In addition to secondary prevention and improvement in cardiovascular prognosis, a focus of modern cardiac rehabilitation has been the drive to improve patient wellbeing and health-related quality of life [2][3][4] .…”
mentioning
confidence: 99%
“…According to different studies, exercise-based cardiac rehabilitation is the most effective preventive program to reduce the burden of cardiovascular risk factors on patients' health [47,48]. As cardiac rehabilitation's role is significant to improve the exercise capacity or quality of life in CVD patients [49], it appears to be necessary for patients to be able to continue their programs during the COVID-19 pandemic. The pandemic has led to the closure of many cardiac rehabilitation centers, stopping patients to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Three reviews that reported little or no difference in mortality for patients with HF participating in CR, however, differed in their findings of reduction in hospital admissions. [43][44][45] A more recent study from Japan did observe significant reductions in both mortality and hospitalizations. 46 Improvements in QoL were observed for patients with HF participating in CR or exercise training programs; however, the effects differed in some regards due to the type of program (home-base or hybrid), 22 instrument used to assess QoL, 45 the type of HF, 47 or if patients experienced a stressful life event.…”
Section: Hf and Arrythmiasmentioning
confidence: 95%